PENILAIAN AUTENTIK DAN RELEVANSINYA DENGAN KUALITAS HASIL PEMBELAJARAN (PERSEPSI DOSEN DAN MAHASISWA IKIP PGRI BOJONEGORO) - Siti Ermawati; Taufiq Hidayat (Jurnal Pendidikan Ilmu Sosial, 2017)
The research aimed to 1) analyze the implementation of authentic assessment at Institute of Teaching and Education (IKIP) PGRI Bojonegoro and 2) identify lecturers and students perception on the impact of authentic assessment toward the quality of students learning outcome. This research was qualitative research using case study approach. The data collection methods were in-depth interview in focus group discussion (FGD) with lecturer and students; and documentation. The data validity examination was triangulation method. The interactive analysis method was used to analyze data. The research found that: 1) Some lecturers of IKIP PGRI Bojonegoro had already implemented authentic assessment method in the learning process. 2) Authentic assessment method was believed very appropriate by the lecturer and students to be implemented in the learning process because this method had many positive impact, especially to students. However, this authentic assessment technique more focused on the learning outcome quality improvement in students than the student’s achievement.